Relationship between Nurses’ Cultural Intelligence - darvish, hassan; nodeh farahani, Majid; khalili, Mina; shabani, Fatemeh (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: Cultural intelligence is an important factor in interaction among various ethnic groups and environments. cultural intelligence may affect job performance.This study examined the relationship between cultural intelligence and job performance of nurses in Eghbal hospital in Tehran,Iran. Materials and Methods: A descriptive correlational design was used. Sample of the research consisted of 70 nurses with at least 1 year of work experience which were randomly selected.Data were collected by using 2 questionnaires: 1- modified Ang and colleagues (2004) questionnaires for cultural intelligence which was translated by Kazimi (2010) and 2- Employee performance questionnaire which was developed by Kazemi (2010) with the reliability of the 0.81. Data were analyzed by SPSS software using Pearson correlation , Multiple regression and Analysis of variance tests. Findings: Results of the study showed that: although there was no significant correlation between total cultural intelligence scores and job performance of nurses but when examining the relationship between cultural intelligence sub categories and job performance a significant correlation was found between behavioral cultural scores with job performance. There was a significant difference between male and female nurses in term of total score of cultural intelligence. Job performance scores was significantly correlated with educational level Conclusion: The results showed tthat behaviorialintelligence may mediate the relationship between cultural intelligence and performance in nurses. Gender was correlated with Cultural Intelligence and educational level was correlated with job performance in nurses . Keywords: Cultural Intelligence, Job Performance, Nurses Ahanchian MR Amiri R Bakhshi M (2012). [Correlation between cultural intelligence and social interaction of nurses. Journal of Health PromotionManagement . 1(2), 44-53. Ang S et al (2007). Cultural intelligence: Its measurement and effects on cultural judgment and decision making, cultural adaptation, and task performance. Management and Organization Review .(3) 335-371. Anges BaloghZoltan Gaal Lajos Szabo. (2011) Relationship between organizational cultural intelligence. Management &Marketing, Challenges for the Knowledge society. Romania.6 (1) 95-110. Briones E et al (2009). Development of a cultural self- efficacy scale for adolescents (CSES-A). Internatinal Journal of Intercultural Relations .(33) 301-312. Crowne K (2008).What leads to cultural intelligence?. Business Horizons . 51)5) 391-399. Faramarz M. Cultural intelligence and adaptability to heterogeneous data.In: Tehran. the first national conference on organizational intelligence / business.2010 Dec 29-30: Tehran , Iran, 2010 P:1-7(persian). . Kazemi M Moghimi S M Amiri A (2010).Studying the Relationship between Cultural Intelligence and Employee’s Performance. European Journal of Scientific Research . 42(3)427-432. [online]<http://www.eurojournals.com/ejsr.htm >.[20 July 2012]. Khashei V Mostame M (2011). [ Cultural intelligence officers, directors, keysuccess factors in the management of the third millennium]. Journal of Cultural Engineering , 5th ( 52,51) 62-72 (Persian). lugo M( 2007).An Examination of cultural and emotional intelligences in the development of global transformational leadership skills.doctoral Dissertation.Walden University.[Online]<books.google.ca/books?isbn=054927541X>.[24July2012]. Moody M C (2007). Adaptive behavior in intercultural environments: The relationship between cultural intelligence factors and big five personality traits. Unpublished doctoral Dissertation of philosophy.George Washington university. Pour Ibrahim S(2005). The relationship between organizational culture & Performance in branches of Mellat Bank inTehran.(Theses )for the degree of Master of Public Administration: Management Faculty of Tehran University (persian). Rahimnia F Mortazavi S Delaram M (2010). the effects of cultural intelligence on job performance of managers (Case Study: Bank of NewEconomics of Tehran. Journal of tomorrow management .( 22). 8th.67-79 (persian). Ravari A et al (2012). Job satisfaction hospital-based practicing nurses: examining the influence of self- expectation, social interaction and organizational situations. Jornal of Nursing Management . 20(4) 522-533. Shin-yih Chen A Yi-Chun Lin & Sawangpattanakul A (2011).The relationship between cultural Intelligence and Performance with the mediating effect of cultural shock: Acase from Philippine laborers in Tiwan. International Journal of Intercultural relations . 35(2) 246-258. Templer K , Tay C & chandrasekar N (2006). Motivational cultural intelligence, realistic job preview, realistic living conditions preview and cross-cultural adjustment. Group and Organization Management .31(1) 154-173.